if α, β, γ are the roots of the equation x^3- 3x + 11 = 0 then find the equation whose roots are (α+β), (β+ γ) and (γ+ α).
Answers
Answer:
x² - 6x + 9
Step-by-step explanation:
If alpha beta gamma are the roots of the equation x2 - 3x + 11 then find the equation whose roots are (alpha + beta)
α & β are roots of x² - 3x + 11
=> α + β = - (-3)/1 = 3 (Sum of roots)
α + β is roots of other equation
let say γ is roots of other equation
so γ = α + β = 3
Sum of roots = γ + γ = 3 + 3 = 6
Products of roots = γ * γ = 3 * 3 = 9
Equation
x² - 6x + 9
or Simply
(x - γ)(x - γ)
= (x-3)(x-3)
= (x -3)²
= x² - 6x + 9
Answer:
Step-by-step explanation:
If α, β, γ are the roots of the equation x^3- 3x + 11 then-:
x³3- 3x + 11 = (x-α)(x-β)(x-γ)
Using the relation between the zeros-:
α+β+γ = -b/a = 0/1 = 0
=>α+β= -γ
=>β+γ= -α
=>γ+α= -β
αβγ = -d/a= -11
αβ+βγ+αγ = c/a = -3
The roots of our required equation are (α+β),(β+γ) and (γ+α) or rather −α,−β and −γ
Our required equation is,
=>[x−(α+β)][x−(β+γ)][x−(γ+α)]=0
∴(x+α)(x+β)(x+γ)=0
∴x³+γx²+βx²+βγx+αx²+γαx+αβx+αβγ=0
∴x²+(α+ β+ γ)x²+(αβ+βγ+γα)x+αβγ=0
∴x3−3x−11=0